РОЛЬ ПАТОЛОГІЇ У СИСТЕМІ МЕДСЕСТРИНСЬКОЇ ОСВІТИ - Ройко, Н. В.; Филенко, Б. М.; Старченко, І. І.; Проскурня, С. А. (Медсестринство, 2021)
Reform of nursing services for a large number of new education and education, hence the advancement of education. The introduction of a bagator system for the education of medical nurses gives the possibility of more and more specific preparation of physicians for the practical protection of health. The concept of non-interruption-free supplemental medical education is implemented through the path of the week of the discipline «Pathology» from the development of typical forms of pathology on a fundamental basis to the analysis of specific, ready-made situations (syndromes).